2008
DOI: 10.1097/gme.0b013e31816b4509
|View full text |Cite
|
Sign up to set email alerts
|

Lipid profile of women with premature ovarian failure

Abstract: Loss of ovarian function at a very young age (POF) coincides with subtle changes in the lipid profile (higher TG levels and marginally lower HDL). Androgens (increased free androgen index and testosterone and decreased sex hormone-binding globulin) are better markers for unfavorable lipid changes compared with estrogen levels or duration of estrogen deprivation in women with POF. Elevated TG levels in combination with increased (free) androgens may be an early manifestation of reduced insulin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 23 publications
3
43
2
4
Order By: Relevance
“…Participating hospitals included all eight university hospitals in the Netherlands and six large regional hospitals. Women suspected to suffer from hypergonadotropic oligo-or amenorrhea were systematically evaluated in the outpatient clinic of each individual hospital, as has been described in previous studies from our group (7,12). For the current study, all women visiting the outpatient clinic for POI were identified (n ¼ 378).…”
Section: Patientsmentioning
confidence: 99%
“…Participating hospitals included all eight university hospitals in the Netherlands and six large regional hospitals. Women suspected to suffer from hypergonadotropic oligo-or amenorrhea were systematically evaluated in the outpatient clinic of each individual hospital, as has been described in previous studies from our group (7,12). For the current study, all women visiting the outpatient clinic for POI were identified (n ¼ 378).…”
Section: Patientsmentioning
confidence: 99%
“…Age positively correlates to BMI, waist circumference, body fat, total cholesterol, LDL cholesterol, triglyceride, leptin, CRP, and glucose levels. Physical activity, despite age, is associated with fewer risk factors for chronic diseases like CVD, type 2 diabetes, and obesity (72). Therefore, regular physical activity may be considered an antidote to these risk factors.…”
Section: Dyslipidemiamentioning
confidence: 99%
“…This risk is more pronounced in those who have never used estrogens. The increased risk of CVD may be due to direct effects on the endothelium [87], or through alterations to traditional cardiovascular risk factors such as adverse effects on lipid profile [88], reduced insulin sensitivity [89] and metabolic syndrome [90].…”
Section: Long-term Effectsmentioning
confidence: 99%
“…This risk is more pronounced in those who have never used estrogens. The increased risk of CVD may be due to direct effects on the endothelium [87], or through alterations to traditional cardiovascular risk factors such as adverse effects on lipid profile [88], reduced insulin sensitivity [89] and metabolic syndrome [90].A recent review of the available evidence has suggested a significant increased risk of stroke associated with POI, with a protective role for estrogen used until the average age of menopause [91]. Additionally, data…”
mentioning
confidence: 99%